Budding of Teak - Bryndum, Knud (Indian Forester, 1969)
Vegetative propagation at the Teak Improvement Center in Thailand is reviewed by summing up the data from budding during the years 1965-67. It is found that the trend is similar to that reported from an experiment in India (Rawat and Kedharnath, 1968), where propagation in April-May is most successful. Fair results are also got from budding in November-December and this period is now preferred for administrative and technical reasons.